Implementasi SPBE Pada Pelayanan Administrasi Kependudukan dan Dampaknya Terhadap Kualitas Pelayanan Publik di Kota Surabaya - Rusmiyati Dewi Safitri; Dewi Casmiwati (Policy and Maritime Review, 2025)
This study aims to analyze the implementation of the Electronic-Based Government System (Sistem Pemerintahan Berbasis Elektronik/SPBE) in population administration services and its impact on the quality of public services at the Department of Population and Civil Registration (Dispendukcapil) of Surabaya City. This research employs a qualitative descriptive approach, with data collected through in-depth interviews with key informants consisting of public service officials and service users, direct observation of digital service processes, and analysis of policy documents related to SPBE implementation. The data were analyzed using an interactive analysis model involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of SPBE has positively contributed to improving the quality of population administration services, particularly in terms of efficiency, accessibility, transparency, and service speed, as well as reducing bureaucratic complexity and face-to-face interactions. Nevertheless, several challenges persist, including disparities in digital literacy among citizens, occasional technical system disruptions, and the need for continuous capacity building of human resources. This study is limited to a single government agency, which may affect the generalizability of the findings. Practically, the results provide insights for local governments in strengthening SPBE implementation through system integration, enhancement of digital competencies, and inclusive service strategies. Socially, improved digital population administration services support equitable access to basic administrative rights for citizens. This study offers empirical value by enriching the discourse on digital governance and public service quality within the context of local government policy implementation in Indonesia.